ChemInform Abstract: A New Series of Borophosphate Phosphor Cd3BPO7:M (M: Ce3+, Tb3+, Mn2+) with Tunable Luminescence and Energy Transfer Properties. Issue 17 (April 2016) - Cao, Xiyu; Liu, Wei; Liu, Shuang; Cao, Lixin; Su, Ge; Gao, Rongjie; Jiang, Yu
Abstract: Cd3 BPO7, Cd3 BPO7 :xCe 3+ (x = 5, 7, 9, 11 mol%), Cd3 BPO7 :yTb 3+ (y = 2, 3, 4, 6, 8, 12 mol%), Cd3 BPO7 .zMn 2+ (z = 0.5, 0.7, 1.15, 2 mol%), Cd3 BPO7 :9 mol%Ce 3+, yTb 3+ (y = 3, 4, 6, 8 mol%), and Cd3 BPO7 :9 mol%Ce 3+, zMn 2+ (z = 0.5, 0.7, 1.15, 2 mol%) are prepared by solid state reactions of stoichiometric amounts of CdO, H3 BO3, NH4 H2 PO4, Tb4 O7, CeF3, and MnCO3 (alumina crucible, 573—1123 K, 4—12 h).